Respon Amerika Serikat dalam Menyeimbangkan Kekuatan Cina Melalui AUKUS dalam Klaim Kedaulatan Cina di Laut Cina Selatan - Santoso, Dimas Idham; Munir, Ahmad Mubarak; Dewanto, Pamungkas Ayudhaning (Department of International Relations, University of Mataram, 2023)
This research aims to analyze the formation of AUKUS as a new defense pact as the United States' response to China's unilateral claim of sovereignty in the South China Sea. The lack of presence of the United States, which for the last few decades has been too busy with its military operations in the Middle East region, has given China more freedom to carry out aggressive maneuvers in the Asia Pacific region which has then created an imbalance of power due to China's military strength being far superior to that of the alliance countries. United States in Asia such as the Philippines and Australia. In this research, a qualitative approach was used which aims to understand the phenomenon of events experienced by the subject through descriptions. Furthermore, this research uses the Balance of Power Theory and the Concept of Detterence as analytical tools to understand the material raised in this research. The results of this research show that AUKUS was formed due to the decline of the United States in various sectors which coincided with the rise of China as a new superpower. It is hoped that the selection of Australia and the UK in this collaboration will provide additional support to pressure China in the South China Sea through short-term and long-term programs.